2004
DOI: 10.1007/s00391-004-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Kognitive Verhaltenstherapie bei Depressionen im Alter

Abstract: Cognitive behavioral group treatment is a well accepted, successful intervention for older adults. Waiting for treatment is problematic. It does not only produce no changes in symptomatology but even leads to worsening of depression in a large number of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This design decision was taken to ensure a significantly large number of patients in both treatment arms to address the primary research question of the study, namely, the specific efficacy of CBT in LLD. However, symptom changes of waiting-list LLD control groups have been reported in the literature, and the effects we observed in both treatment arms of our study are substantially larger [15, 3235]. A further limitation is that treatment integrity was not assessed throughout all rated videos by multiple raters using a measure previously shown to be reliable and valid as well as in this sample.…”
Section: Discussionmentioning
confidence: 63%
“…This design decision was taken to ensure a significantly large number of patients in both treatment arms to address the primary research question of the study, namely, the specific efficacy of CBT in LLD. However, symptom changes of waiting-list LLD control groups have been reported in the literature, and the effects we observed in both treatment arms of our study are substantially larger [15, 3235]. A further limitation is that treatment integrity was not assessed throughout all rated videos by multiple raters using a measure previously shown to be reliable and valid as well as in this sample.…”
Section: Discussionmentioning
confidence: 63%
“…The pooled remission rates after completion of therapy were 0.5174 for ICBT and 0.6090 for FCBT. The pooled spontaneous remission rate in the absence of acute treatment for patients in the depressed state was 0.0123 [ 42 , 63 – 67 , 71 , 72 ]. Relapse rates were 0.0064 after full remission (after treatment completion) [ 39 47 ] and 0.0202 after spontaneous remission [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent review, Jonsson et al46 examined 22 RCTs that had evaluated the effectiveness of different forms of psychotherapy in older depressed patients, and they found that problem-solving therapy had a large and heterogeneous effect size compared with usual care, whereas the evidence for the effectiveness of cognitive behavioral therapy (CBT) and reminiscence therapy (also known as life review therapy) was insufficient due to small study numbers, heterogeneity of interventions, and a high risk of bias. Hautzinger and Welz47 compared CBT with a waitlist control group and found that CBT was superior to the control in reducing depressive symptoms and in producing remission rates posttreatment and at follow-up intervals in depressed older outpatients. The effectiveness of psychotherapy in older depressed patients was also supported by findings from Peng et al48 who found that CBT and reminiscence therapy were both more effective than placebo with no significant difference between either form of therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pharmacotherapy, psychotherapy should also be provided to patients with LLD as it has been found to be efficacious, especially in the form of individual sessions of CBT and problem-solving therapy 47,48. As no potential pharmacological interaction has to be considered, psychotherapy is safe in the elderly.…”
Section: Discussionmentioning
confidence: 99%